Penetapan Kadar Flavonoid Ekstrak Daun Kalapapa (Vitex Pinnata L.) dengan Tingkatan Fraksi - Elieser, Michael; Rohama, Rohama; Alawiyah, Tuti; Hakim, Ali Rakhman (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The background to this research is that one of the plants that is often used by people in the interior of Central Kalimantan, specifically in the village of Tumbang Talaken, is the Kalapapa plant. The Dayak tribe community in the Tumbang Talaken area of Central Kalimantan uses Kalapapa leaves as a trusted medicinal plant and is used as a traditional medicine to heal wounds using the simple method of crushing the leaves and applying them directly to the surface of the injured skin. Kalapapa leaves contain flavonoids, alkaloids, saponins and tannins. In the context of wound healing, flavonoids have an important role in increasing the speed of wound healing. The aim of the research was to determine the levels of total flavonoid compounds in the distilled water fraction, ethyl acetate fraction, and n-hexane fraction of kalapapa leaf extract (Vitex Pinnata L.). The research method used was a descriptive method by looking at the results of qualitative data, namely a reaction test. color and quantitative data, namely using Uv-Vis spectrophotometry to see total flavonoid levels. The results of the qualitative analysis research showed that the color test identification of kalapapa leaf extract (Vitex Pinnata L.) was positive for containing flavonoids. The results of quantitative analysis using Uv-Vis spectrophotometry showed that the total flavonoid content with 96% ethanol extract was 43.95 QE/g, distilled water with a value of 42.14 QE/g, ethyl acetate with a value of 196.8 QE/g, and n -hexane with a value of 54.42 QE/g or 96% 4.39% ethanol extract, distilled water 4.21%, ethyl acetate 19.68%, and N-hexane 5.44%. The highest total flavonoid levels were found in the ethyl acetate fraction. The research conclusion is that kalapapa leaf extract at fraction levels contains flavonoid compounds with total flavonoid levels in the ethanol extract of 96%, distilled water fraction, ethyl acetate fraction and n-hexane fraction of 43.95 mg QE/g or 4.39%; 42.14 mg QE/g or 4.21%; 196.8 mg QE/g or 19.68%; and 54.42 mg QE/g or 5.44%.